2008
DOI: 10.1016/j.marenvres.2008.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial gene and protein expression in grass shrimp, Palaemonetes pugio, exposed to chronic hypoxia

Abstract: Spatial and temporal increases of hypoxia in estuaries are of major environmental concern. Since mitochondria consume most of the oxygen in the cell, we examined the potential role of mitochondrial gene and protein expression in adaptation to chronic hypoxia in the grass shrimp Palaemonetes pugio. Grass shrimp were exposed to DO levels slightly above and below the critical pO(2), 1.8 mg/L, for P. pugio, and hypoxia-induced alterations in gene expression were screened using custom cDNA macroarrays. Mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The CO genes' expression and the activity of the enzyme are known to be affected by external factors. In crustacean species, such as the grass shrimp Palaemonetes pugio, the gene expression of subunits CO1 and CO2 is positively or negatively regulated by low dissolved oxygen concentrations in water (Brouwer et al, 2008). References and further reading may be available for this article.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…The CO genes' expression and the activity of the enzyme are known to be affected by external factors. In crustacean species, such as the grass shrimp Palaemonetes pugio, the gene expression of subunits CO1 and CO2 is positively or negatively regulated by low dissolved oxygen concentrations in water (Brouwer et al, 2008). References and further reading may be available for this article.…”
Section: 4mentioning
confidence: 99%
“…Also, significant changes in the amount of mRNA from the mitochondrial-and nuclear-encoded subunits of the ATP synthase were detected at different molt stages and tissues, according to the energy requirements of each stage and the specific requirements of the function of each tissue (Muhlia-Almazan et al, 2008). Chronic exposure to severe hypoxia (1.5 mg/mL during 7 days) also causes the increased transcription of mitochondrial-encoded genes, such as the 16S, CO1, and CO2 subunits from the cytochrome C oxidase in the grass shrimp Palaemonetes pugio (Brouwer et al, 2008). To date, microarray technologies have revealed a set of genes that are up-and down-regulated in P. pugio during chronic, acute and moderate hypoxia; the results revealed that various genes encoding mitochondrial proteins were affected (Li & Brouwer, 2009).…”
Section: How Do Invertebrates Face Hypoxia?mentioning
confidence: 99%
“…Following the same procedure, we determined in individual cells the expression levels of several selected genes involved in hypoxia response, including mitochondrially-encoded COXI , COXIII , and CYTBI [43][45], and the VEGF , MT3 , ANGPTL4 and PTGES genes encoded by the nuclear DNA, with 16S rRNA and 28S rRNA were used as internal controls [31], [38], [46][48].…”
Section: Resultsmentioning
confidence: 99%
“…Three mitochondrially encoded genes, COXI , COXIII and CYTBI , were selected for expression analysis due to their significant role in mitochondrial function and involvement in hypoxia response [44], [45]. First, we compared the relative expression levels of these genes between normoxic and hypoxic conditions in bulk cell samples using mitochondrial 16S rRNA as an internal reference.…”
Section: Resultsmentioning
confidence: 99%
“…Exposures and animal sampling were performed as previously described [88,89]. Cadmium (0.3 mg/L) was administered to sheepshead minnow larvae at 24 hours post hatch via precision syringe pumps in an intermittent flow-through system [90].…”
Section: Methodsmentioning
confidence: 99%